Effects of climate change and human activities on runoff and sediment inputs of the largest freshwater lake in China, Poyang Lake. Issue 14 (26th October 2017) - Gu, Chaojun; Mu, Xingmin; Gao, Peng; Zhao, Guangju; Sun, Wenyi; Li, Pengfei
ABSTRACT: The nonparametric Mann-Kendall test and the Pettitt test were employed to examine the change trends and shifts of runoff and sediment input to Poyang Lake between 1961 and 2013. Water balance and linear regression models were used to evaluate the impacts of climate variability and human activities on the runoff and sediment discharge changes. The results showed that runoff inputs to the lake had insignificant temporal trends and change points, while sediment inputs had significant decreasing trends, with an abrupt change in 1989. Quantitative assessment demonstrated that human activities led to a small decrease (5.5%) in runoff inputs to the lake, and a dramatic (121.4%) decrease in sediment inputs to the lake between the reference period (before the change point) and the human-influenced period (after the change point). This work provides a useful reference for future policy makers in water resource utilization and environmental safety of the Poyang Lake basin.